Теоретические основы развития инновационного маркетинга в страховых компаниях - Смирнова, Е.А. (Культура народов Причерноморья, 2013)
В статье рассмотрены теоретические основы понятия инновационного маркетинга и маркетинга инноваций. Определено, что инновационный маркетинг выступает как маркетинговая деятельность, направленная на разработку, внедрение и распространение инноваций, что позволит страховым компаниям повысить конкурентоспособность, прибыльность а также сформировать и улучшить эффективность продаж страховых продуктов. У статті розглянуті теоретичні основи поняття інноваційного маркетингу і маркетингу інновацій. Визначено, що інноваційний маркетинг виступає як маркетингова діяльність, яка направлена на розробку, впровадження та розповсюдження інновацій, що дозволить страховим компаніям підвищити конкурентоспроможність, прибутковість а також сформувати і поліпшити ефективність продажів страхових продуктів. World experience of development of economy proves presently, that rational combination of marketing and innovative activity allows operatively to find not enough the satisfied consumer queries, or to form them (for on principle new commodities), develop, produce and move forward new (modernized) products at the market. The analysis of domestic and foreign experience shows that conception of the innovative marketing is perspective direction of development of insurance companies, for this reason actual is a question of forming and increase of efficiency of sales of insurance products with the use of new technologies of marketing. The decision of this question requires introduction of modern innovations in marketing activity of insurance company, which are successfully used in the insurance marketing. It is necessary to examine the innovative marketing as a type of activity, directed on optimization and control after innovative and sale activity of insurance company, that will allow to occupy strategically a vantage-ground at the insurance market, and also to increase the income of insurance company. In modern terms by the prospects of development of the insurance marketing, taking into account the features of the presented approaches there is active application of the innovative marketing, and in order that to attain efficiency of introduction of marketing’s innovations the selection of the followings stages is needed: - search and analysis of idea of new insurance product;  collection of information about a potential market and segment of future product, and also analysis of competition on him; - actuarial calculations of perspective of the chosen segment; - determination of «technical side» of new product; - development of marketing strategy for a new insurance product. Thus, the innovative marketing is one of important directions of development of the insurance marketing, and also comes forward as marketing activity, directed for development, introduction and distribution of innovations, that will allow insurance companies to promote competitiveness, profitability, and also to form and improve efficiency of sales of insurance products